Pakistan Poverty Trends, Scenarios and Drivers - Lopez-Calix, Jose (World Bank, Washington, DC, 2014)
This policy paper examines recent poverty trends in Pakistan. Official statistics continue to indicate strong poverty reduction through 2010-11, thanks in large part to policies and investments that boosted productivity in the non-agricultural sector. Poverty fell a bit more than other countries with similar rates of growth, as growth was slightly pro-poor and also benefited the bottom 40 percent. Alternative indicators such as access to public services have also improved, though at a slower rate since 2008 the year of twin global and domestic crises that hardly hit Pakistan. While increased productivity among non-agricultural workers has been a key factor driving poverty reduction, cash transfers through the Benazir Income Support Program (BISP) and workers' remittances from abroad also made moderate contributions. Simulations suggest that higher growth rates would further accelerate poverty reduction, but would have smaller effects on attaining other Millennium Development Goals. Despite this progress on poverty reductions, a major concern is that large numbers of people still remain concentrated just above the poverty line, thus remaining vulnerable to even small shocks, like natural disasters. Furthermore, the Pakistani economy has failed to create enough salaried and non-agricultural jobs, and female labor force participation remains unusually low by regional and worldwide standards. BISP cash transfers have helped reduce poverty and are well-targeted, but their coverage still is small; while remittances accrue mainly to non-poor households. If Pakistan can address these remaining constraints and also achieve more rapid growth, in particular with less frequent load-shedding and high levels of investment in human capital, the labor market has the potential to absorb new workers and further accelerate the improvement in living standards for the poor and near-poor.